Development and evaluation of Al2O3–ZrO2 composite processed by digital light 3D printing. Issue 7 (May 2020) - Zheng, Tianqi; Wang, Wei; Sun, Jinxing; Liu, Jing; Bai, Jiaming
Abstract: Digital Light Processing (DLP) is a promising approach to fabricate delicate ceramic components with high-fidelity structural features. In this work, the alumina and zirconia/alumina ceramic suspensions with low viscosity and high solid loading (40 vol%) were prepared specifically for DLP 3D printing. After debinding and sintering, the final parts were obtained without any defects. The surface morphologies and mechanical properties of alumina (Al2 O3 ) and zirconia toughened alumina (ZTA) composites were investigated and the results showed that the final parts exhibited high relative densities and good interlayer combination at the sintering temperature of 1600 °C. Comparing with the Al2 O3, the ZTA composites exhibited significantly enhanced density (99.4%), bending strength (516.7 MPa) and indentation fracture toughness (7.76 MPa m 1/2 ).